Competitiveness Analysis of Istanbul Financial Center - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
The main purpose of this article is to compare Istanbul Financial Centre with selected twelve centres taking into consideration the banking system, the financial markets and instruments in micro perspective. These selected financial centres are Dubai, Frankfurt, Hong Kong, Kuala Lumpur, London, Moscow, New York, Paris, Shanghai, Singapore, Tokyo and Toronto. All financial centres are compared with Istanbul based on by using ranking analysis. Various characteristics of the financial system are taken. Nine indicators are used for the banking sector, whereas 13 indicators are used for the financial markets. The indicators are used as the average of the values between 1992 and 2012 in the ranking analysis. Our research question is that: What is the competitiveness of Istanbul among International Financial Centres. The contribution of this study is analysing competitiveness potential of Istanbul Financial Centre and proving the importance of banking sector and the capital markets on the size of the financial system in financial centres. As a result, Istanbul Financial Centre has not competed yet with compared financial centres. By considering the characteristic of the financial system in global and regional centres, Istanbul will be grown and developed first as a national financial centre and, then as a regional and international financial centre by implementing right strategies. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: financial centre; financial system; banking system; financial market; social network analysis; FRANKFURT; AMSTERDAM